UPAYA MENINGKATKAN MINAT BELAJAR SISWA HINDU PADA PASRAMAN GIRI AJI SENGKONGO KABUPATEN LOMBOK BARAT - Jeki Waemese; Gusti Ngurah Ketut Putera; I Wayan Rudiarta (Guna Widya: Jurnal Pendidikan Hindu, 2023)
This research is motivated by the phenomenon that the learning process that takes place at the Giri Aji Sengkongo pasraman is less attractive to students. Interest as a form of motivation should be an energy that is always present in an effort to improve the quality of education. Students' interest in learning is very important because without students' interest in participating in learning, the material provided will not arrive in its entirety. This study aims to reveal the factors causing the lack of interest in learning Hindu students at the Giri Aji Sengkongo pasraman and describe the efforts to increase the learning interest of Hindu students at the Giri Aji Sengkongo pasraman. This research is a qualitative research with data collection using non-participant observation techniques, structured interviews and documentation studies. The data that has been collected is then analyzed by means of data reduction, data verification, and conclusion drawing. The theory used in the data analysis of field findings is Maslow's theory of motivation. The research findings indicate that several factors cause the students' lack of interest in learning at the Giri Aji Sengkongo boarding school in the form of lack of infrastructure, students get bored quickly, monotonous learning methods, and lack of teaching staff. Furthermore, the efforts made to overcome this are teachers always motivating students, intensive communication between teachers and students' parents, giving pocket money, reward and punishment, requesting assistance, empowering stakeholders.